Blepharospasm, Oromandibular Dystonia, and Meige Syndrome: Clinical and Genetic Update - Ma, Hongying; Qu, Jian; Ye, Liangjun; Shu, Yi; Qu, Qiang (Frontiers in Neurology, 2021)
Meige syndrome (MS) is cranial dystonia characterized by the combination of upper and lower cranial involvement and including binocular eyelid spasms (blepharospasm; BSP) and involuntary movements of the jaw muscles (oromandibular dystonia; OMD). The etiology and pathogenesis of this disorder of the extrapyramidal system are not well understood. Neurologic and ophthalmic examinations often reveal no abnormalities, making diagnosis difficult and often resulting in misdiagnosis. A small proportion of patients have a family history of the disease, but to date no causative genes have been identified to date and no cure is available, although botulinum toxin A therapy effectively mitigates the symptoms and deep brain stimulation is gaining increasing attention as a viable alternative treatment option. Here we review the history and progress of research on MS, BSP, and OMD, as well as the etiology, pathology, diagnosis, and treatment.